Extraction of Protein-Bound ATP and ADP from Human Platelets in Plasma - Beurling-Harbury, Christina; Harbury, Pehr B (Thrombosis and Haemostasis, 1990)
Actin is the major ATP and ADP binding protein in platelets, 0.9–1.3 nmol/108 cells, 50–70% in the unpolymerized state. The goal of these experiments was to develop a method for extracting all protein-bound ATP and ADP from undisturbed platelets in plasma. Extraction of actin-bound ADP is routine while extraction of actin-bound ATP from platelets in buffer has been unsuccessful. Prior to extraction the platelets were exposed to 14-C adenine, to label the metabolic and actin pools of ATP and ADP. The specific activity was determined from the actin-bound ADP in the 43% ethanol precipitate. Sequential ethanol and perchlorate extractions of platelet rich plasma, and the derived supernatants and precipitates were performed. ATP concentrations were determined with the luciferase assay, and radioactive nucleotides separated by TLC. A total of 1.18 nmol/108 cells of protein-bound ATP and ADP was recovered, 52% ATP (0.61 nmol). The recovery of protein-bound ADP was increased from 0.3 to 0.57 nmol/108 cells. This approach for the first time successfully recovered protein bound ATP and ADP from platelets in a concentration expected for actin.